2012
DOI: 10.1016/j.ecss.2012.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Free-living and particle-associated prokaryote metabolism in giant kelp forests: Implications for carbon flux in a sub-Antarctic coastal area

Abstract: Extensive beds of large subtidal kelps are characteristic of many temperate and subpolar coastlines. They provide habitats for a wide range of other species and are sites of high primary production that generate large quantities of water-borne particles and dissolved organic compounds that support distinctive communities of prokaryotes. We measured prokaryotic metabolism along transects from the shore to the outside of three giant kelp forests (Macrocystis pyrifera) located in the shelf waters of the Prince Ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 69 publications
0
4
1
Order By: Relevance
“…In a tidal estuary exhibiting high loads of suspended matter, particle-attached prokaryotes can reach up to 80% of total abundance (De Souza et al 2003). It has previously been observed that particle-attached prokaryotes were more active than free-living cells (Grossart et al 2007a, 2007b, Schapira et al 2012. Although in our study no difference could be evidenced in prokaryote abundance between water layers, the proportion of J o u r n a l P r e -p r o o f particle-attached cells may have been higher in the bottom compared to other layers, due to higher loads of SPM (Fig.…”
Section: Prokaryotic Compartment Stratificationcontrasting
confidence: 54%
“…In a tidal estuary exhibiting high loads of suspended matter, particle-attached prokaryotes can reach up to 80% of total abundance (De Souza et al 2003). It has previously been observed that particle-attached prokaryotes were more active than free-living cells (Grossart et al 2007a, 2007b, Schapira et al 2012. Although in our study no difference could be evidenced in prokaryote abundance between water layers, the proportion of J o u r n a l P r e -p r o o f particle-attached cells may have been higher in the bottom compared to other layers, due to higher loads of SPM (Fig.…”
Section: Prokaryotic Compartment Stratificationcontrasting
confidence: 54%
“…Another possibility is the involvement of some of these Flavobacteria in the degradation of macroscopic algae, such as the Phaeophyta kelps (brown algae), which are members of the order Laminariales. Extensive beds of large subtidal kelps are typical of the temperate Pacific Northwest coastline, they generate large quantities of water-borne particles and dissolved organic compounds that support distinctive communities of prokaryotes (Schapira et al, 2012). Genomes of many Flavobacteria, including the Flavobacterales sp.…”
Section: Discussionmentioning
confidence: 99%
“…During nearshore seasonal upwelling events, this salinity intrusion often carries coastal phytoplankton blooms, thereby supplying ocean-derived POM to the lower estuary (Kudela et al, 2005 ; Roegner et al, 2011 ; Herfort et al, 2011a ). Extensive beds of large subtidal kelps (the brown algae Phaeophyta) that are a typical feature of the temperate Pacific Northwest coastline (Schapira et al, 2012 ) also supply POM along the coastal margin.…”
Section: Origin and Fate Of Particulate Matter In Estuariesmentioning
confidence: 99%
“…Particle-attached bacteria are often observed to be larger than free-living bacteria, likely due to greater substrate accessibility compared to the surrounding waters (Alldredge et al, 1986 ; Simon et al, 2002 ). Many reports also document higher activity on a per-cell basis for particle-attached compared to free-living bacteria (Fandino et al, 2001 ; Grossart et al, 2003 , 2007 ; Schapira et al, 2012 ). Others have, however, noted higher activities in free-living populations (Alldredge et al, 1986 ; Martinez et al, 1996 ; Schapira et al, 2012 ), thus associated environmental parameters and particle properties are likely to be important determinant factors.…”
Section: Differences In Community Composition and Metabolic Propertiementioning
confidence: 99%